Suicidal ideation and behavior among subjects with substance abuse disorder related to pregabalin - Abdallah Saad Ibrahim (Middle East Current Psychiatry, 2022)
Abstract Background Although pregabalin abuse is increasing worldwide and may be associated with increased suicidal ideation and behavior, few studies were done in Egypt searching for the effect of pregabalin on suicide. Eighty-three patients meeting DSM-IV criteria for substance abuse disorders related to pregabalin were identified from the addiction clinic of EL Khanka Psychiatric Hospital in Egypt for this observational cross–sectional study. We intended to assess suicidal ideation and behavior in patients with substance abuse disorder related to pregabalin and to identify the effects of other comorbid substances of abuse. All participants were subjected to semi-structured interview designed to collect and identify the socio-demographic data and patterns of substances 'use ,The Structured Clinical Interview for DSM-IV Axis I Disorders to diagnose patients with substance abuse disorder “related to pregabalin,” Beck Scale for Suicidal Ideation for assessment of suicidal ideation and behavior and urine screening test for pregabalin and other substances of abuse. Results Most of participants used pregabalin continuously {86.7%}. More than seventy nine percent of the patients abused both pregabalin and other substances, tramadol 67.4%, heroin 66.3%, cannabis 65.1%, other drugs 44.6%, and benzodiazepines 27.7%. Screening urine test was positive in 62.7% of participants most frequently was heroin 41% and cannabis 34.9%. No suicidal ideation was found in 67.4%, 19.3% had low risk of suicide, and 13.3% had high risk of suicide so total participants who had suicidal ideation were 32.6%. There was statistical significant increase in risk of suicide among patients who were continuously abusing pregabalin and who had positive pregabalin urine test. There was significant positive correlation between Beck Suicidal Ideation score and duration of abusing pregabalin, maximum and daily dose of pregabalin. Also, there was a statistical significant relation between suicidal ideation and associated tramadol abuse and this was positively correlated with dose and duration of tramadol abuse. Conclusions About one third of patients abusing pregabalin had a risk of suicide and this risk increased with associated tramadol abuse so pregabalin abuse is dangerous like other substances of abuse and must be used with caution under strict medical supervision